Serum metabolomic signatures of vegetarians relative to omnivores in a Chinese cohort: associations with cardiometabolic risk factors - Yao, Die; Qian, Linxi; Jin, Yizhou; Wang, Xiaodi; Lu, Xintong; Song, Fangfang; Shen, Xiuhua (Frontiers in Nutrition, 2025)
IntroductionThis study aimed to compare serum metabolomic profiles between vegetarians and omnivores in a Chinese cohort and investigate their associations with cardiometabolic risk factors, including obesity, blood pressure, lipid profiles, and glucose metabolism.Materials and methodsA cross-sectional study included 444 participants (222 vegetarians and 222 omnivores) matched by age and sex. Serum metabolomic profiling was performed using ultra-performance liquid chromatography–tandem mass spectrometry. Correlation analyses and multivariate linear regression models were employed to examine the associations between metabolites and cardiometabolic risk factors, adjusting for potential confounders such as age, sex, physical activity, and dietary patterns.ResultsSeventeen key differential metabolites were identified, with 11 upregulated (e.g., maleic acid, methylcysteine, citric acid, indolepropionic acid [IPA]) and 6 downregulated (e.g., docosahexaenoic acid, eicosapentaenoic acid, creatine) in vegetarians compared to omnivores. After adjusting for covariates, metabolites such as methylcysteine, aconitic acid, and IPA were inversely associated with obesity indices (BMI, waist-to-hip ratio, body fat percentage), blood pressure, and lipid profiles, while creatine showed positive associations with obesity markers. Notably, IPA was linked to reduced systolic and diastolic blood pressure, and aconitic acid correlated with improved insulin sensitivity. Dietary analysis revealed that IPA and methylcysteine were positively associated with plant-based foods such as whole grains, millet, and legumes, while docosahexaenoic acid and eicosapentaenoic acid showed strong positive correlations with animal-based foods, particularly seafood.ConclusionVegetarian diets are associated with unique serum metabolomic profiles that may improve cardiometabolic health.